Semantic Model Representation in Colombian Computer Law - Rojas Moreno, Juan Fernando; Gaona, Paulo; Barón, Julio (TECCIENCIA, 2020)
Ontological representations in diﬀerent domains of reality enable the creation of conceptual relationships that can be coded to reuse and share knowledge. The present article proposes a semantic model representation in Colombian computer law through the methodological process of Methontology. This proposal is the ﬁrst approximation of a legal semantic model in Colombia that allows structuring searches founded on inferences to obtain information with a high degree of rele- vance for lawful expert users. The queries of the proposed model are made by se- mantic content, contrasting to the current legal information search engines which execute queries by textual coincidence.